Religiosity of Malays living in Malaysian rural areas: an analytical survey - Abdul Rashid Moten,; Saodah Wok, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Religion affects an individual’s perception and the way in which people behave. The Malays in Malaysia observe religious rites and rituals and portray Islamic values in their behavior. Based upon a sample survey, this study examines respondents’ belief in the deity, the frequency and intensity of their involvement in religious rites and rituals, and their devotion to religious ceremonies. It is hypothesized that a person with a higher level of religiosity is more likely to align his/her behavior in compliance with religious belief and practices. This study finds that the Malays are polite in their behavior to their parents, try to help others, refrain from taking interests on loans to friends, and the like. Islam seems to influence all aspects of the behavior of the Malays in Malaysia. Most of them would abide by most of the dictates of their religion in their dealings with others. Religiosity is not significantly related to age, education, gender, and marital status. However, the rural population consistently scores high on all measures of religiosity.